Leadership : theory and practice - Northouse, Peter Guy. (Thousand Oaks, Calif. : Sage, 2004)
"The Third Edition of this bestselling text reviews and analyzes the foremost leadership theories, giving special attention to how each theoretical approach can be applied in real-world organizations. For anyone seeking to explore how an understanding of leadership theory can inform and direct the way leadership is practiced, Leadership: Theory and Practice is an indispensable tool. Adopted as a textbook at over 250 colleges and universities, this bestselling volume is equally useful for private-sector leadership development training programs."--BOOK JACKET.
Introduction -- Trait approach -- Skills approach -- Style approach -- Situational approach -- Contingency theory -- Path-goal theory -- Leader-member exchange theory -- Transformational leadership -- Team leadership / Susan E. Kogler Hill -- Psychodynamic approach / Ernest L. Stech -- Women and leadership / Julie Indvik -- Leadership ethics.
Includes bibliographical references and indexes.
Keywords: Leadership; Leadership -- Case studies; Leadership; Leiderschap; Leadership; 2; Leadership -- Case studies; Leadership; Case studies